PROSES PRODUKSI GLISERIN SEBAGAI BAHAN PENOLONG DENGAN KLASIFIKASI ABC DAN MIN MAX STOCK DI PT. X - Yuliana Miranda Syafrizal,; Masdania Zurairah,; Rahmad Rezeki, (Jurnal Cakrawala Ilmiah, 2022)
The Main problem why companies keep raw material in quantities is as a safety stock, in chase of delay in delivery from supplier so the process of production process does not stop. Inventory control of auxiliary raw materials aims to achieve optimal efficiency and efectiveness in the supply of raw materials so that there is no excess and shortage of inventory stock. So this study aims to determine whether the amount of stock the raw materials in PT. PHPO KIM - II has been efficient when compared with the result of calculation by using MRP Method. This study will be done on four supporting raw materials that used for the glycerine manufacturing process are; HCl, Ca(OH)2, Filter Aid, NaOH.